Perkembangan Perguruan Tinggi Islam di Indonesia (Kasus STAIN, IAIN, UIN Dan Perguruan Tinggi Islam) - Afrizal Afrizal (Berkala Ilmiah Pendidikan, 2022)
The development of Islamic universities in Indonesia began with the opening of the Islamic College (STI) in Jakarta in July 1945 before Indonesia's independence. After the formation of STI changed to UII (Islamic University of Indonesia). The next development of the religious faculty of UII was nationalized as PTAIN (State Islamic College), then the next phase came IAIN and STAIN, besides that, private Islamic higher education emerged, both in the form of universities, institutes, and high schools. Expansion of Islamic Higher Education as an effort to develop Islamic higher education in realizing higher quality and qualified Islamic higher education institutions and able to compete with PTUs in Indonesia. UII, UII Faculty of Religion became PTAIN, PTAIN and ADIA became IAIN, then IAIN became UIN. The conversion of IAIN/STAIN to UIN is a positive and constructive response to the challenges of a globalized world of education so as to produce graduates who have competitive adventage, reliable and strong competitiveness in facing the challenges of the times.